Effect of storage temperature on shelf life of standardized buffalo milk Ujani basundi (African Journal of Dairy Farming and Milk Production, 2013)
The effects of storage of buffalo milk Ujani basundi, incorporated with or without potassium sorbate (0.1% w/w) and with or without cardamom (0.1% w/w) under ambient (30±1°C) and refrigerated temperature (5±1°C) over a period of 20 days were s tudied. The physicochemical as well as sensory quality of stored product samples were studied. The stored product samples at refrigerated and ambient temperature with potassium sorbate gave shelf life up to 20 and 10 days respectively. The product stored with cardamom gave best flavor score in both the temperature.